Lobbying Success in the European Union - Daniel Rasch (2018)
Having information is key for most political decisions – both for decision-makers and societal actors. This is especially crucial in democratic countries where external stakeholders are invited to participate in decision-making pro- cesses. Assuming that every actor that gets involved in decision-making processes has a particular lobbying goal, there is a